THE LEGAL NATURE OF THE CORPORATE CONTRACT IN U. S. LAW (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In Uzbek civil law not so long ago a new institute - corporate agreement - has emerged, the reasons for the appearance of which in the legislation differ from those that have developed in the business activities of corporations on the territory of the USA. The subject of consideration of this article is the regulation of shareholder agreements by the laws of individual states of the USA. The relevance of this topic is due to the unceasing disputes about the nature of the corporate agreement and its role in the management of the joint-stock company. The USA became the first country in the law of which the corporate agreement appeared. The author considers the reasons that prompted state legislators to introduce provisions on shareholder agreements into the laws on business corporations. Close attention in the article is paid to closed corporations and their differences from business corporations, as the first agreements began to be concluded by shareholders of closed business corporations. It is noted that not all state laws recognize the closed corporation. In order to examine in detail the content of shareholder agreements, the governance structure of an entrepreneurial corporation, which does not involve shareholders in its management, is examined. All management is concentrated in the hands of the board of directors and its appointed managers. Today, such a situation is no longer in the best interest of shareholders. Shareholders realize their desire to manage the corporation and participate in the distribution of profits by entering into shareholder agreements. Analyzing state legislation, the author identifies three types of shareholder agreements, two of which were not previously known to the common law. Attention is drawn to the fact that all norms regulating shareholders' agreements are contained in the laws on business corporations. It is these laws, referred to corporate law, that determine the types, form, and duration of shareholder agreements, as well as their terms and relationship to the provisions of the corporation's articles of incorporation.